Plataforma para estructuración de cursos adaptativos basado en los estilos de aprendizaje activo, reflexivo, teórico y pragmático utilizando técnicas de inteligencia artificial. - Palacios Mora, Carolina Elizabeth (2016)
Today it has acquired a great interest in determining how students learn and acquire knowledge independently, as today when learning how to learn is one of the demands of the context, it is necessary that learning styles are diagnosed students, which can target more clearly the development of autonomy. Under this scenario, the main objective of the work is based on providing degree courses based on Adaptive Active learning styles, Reflective, Pragmatic Theory and using AI techniques. For this analysis was performed based on investigative techniques such as surveys and interviews conducted with teachers and students of the School of Computer Engineering of the National University of Loja and neural networks used with WEKA Framework in order to design a model that allows direct experimentation with the knowledge base. The proposed neural network model was integrated and codified as a service on the application server to achieve the identification of the different learning styles of the contents entered into the system, the same that was validated in a real educational scenario. For the validation process was established and created a programming course, so that an experimental group made up of university students interact in the virtual course and based on this, the model implemented in the application server generates results.